ANALISIS EFEKTIVITAS PROGRAM MBKM-Kampus Mengajar Angkatan I Di SDN Wonokerto 3, Kabupaten Jombang, Jawa Timur - Dewi Casmiwati; Vera Nurdayanti (PUBLIC CORNER, 2023)
AbstractThe Teaching Campus Program is part of the Merdeka Belajar-Kampus Merdeka (MBKM)policy program which aims to move towards the success of national education and assistteachers and principals in the implementation of learning activities in the midst of the Covid19 pandemic. One of the elementary schools where MBMK takes place is SDN Wonokerto 3,Wonosalam, Jombang, East Java. The purpose of this study was to analyze the effectivenessof the implementation of the MBKM Program for Teaching Campus Batch I. The researchmethod used was descriptive qualitative approach. The data collections were observations,interview, documentation, and literature studies. The analysis in this study was based on thetheory of program effectiveness according to Campbell J.P. (1989). The results of this studyshow that the teaching campus program has not been effective in implementation. This wasseen from (1) the success of the program, (2) the success of the target, (3) satisfaction withthe program, (4) the level of output and input, and (5) the overall program had not beenachieved optimally. This research recommends to improve facilities and infrastructure, andspecial assistance for teachers to support the process of teaching and learning activities inschools.Keywords: Effectiveness, Campus, Teaching, Jombang